Preparation and characterization of α-alumina nanoparticles and α-alumina-based polypropylene nanocomposites - Mirjalili, Fatemeh (2010)
In this study, nano α-alumina particles were synthesized by a sol–gel method. Sodium dodecylbenzen sulfonate (SDBS) and sodium bis-2-ethylhexyl sulfosuccinate (Na (AOT)) were implemented as the surfactant stabilizing agents.The prepared solution was, then, stirred at different times (24, 36, 48 and 60 hours) at 60ºC. SDBS application proved to present a better nanoparticle dispersion and finer particle size as compared to Na (AOT). The finest particle size ranging from 20-30 nm was obtained at 48 hour stirring time with SDBS surfactant being at 1200°C. Similarly, the effect of temperature on production of α- nano alumina was put under investigation. The process included milling the mediums and uniformly mixing them with the hydrous alumina during grinding as well as utilizing ZnF2 additives in order to reduce the transformation temperature and to modify the alumina particles shape. The non agglomerated nano plate like alpha alumina particles were observed to be formed at their finest size (15-20nm) at 950°C. Later, self–produced nano -alumina particles were utilized to develop the PP/nano α-Al2O3 composite. This study aimed to investigate the mechanical, thermal and morphological properties of PP/ nano α-Al2O3 composite with and without addition of dispersant. Polypropylene matrix was filled and mixed with different weight percentages of nano α- alumina particles using a Haake internal mixer. Mixing was performed at 170ºC and 50 rpm for the rotor speed. Mechanical tests such as tensile, flexural and Izod impact tests were found to increase by the addition of content of nano α-Al2O3 as well as the dispersant. Maximum tensile strength (~16 %) and tensile modulus (~27%) can be attributed to the increase of nano α-Al2O3 loading from 1 to 4 wt % into PP matrix. Flexural analysis showed maximum values of 50.5 and 55.88 MPa for flexural strength and 1954 and 2818 MPa for flexural modulus for PP/ nano α-Al2O3 composite with and without dispersant ,respectively. Notched-Izod impact energy showed an increase up to ~ 43 J/m for the PP/4wt% nano α-Al2O3 composites. Higher concentration of nano α-Al2O3 loading resulted in a reduction of mechanical properties due to nano α-Al2O3 agglomeration. Dynamic mechanical analysis indicated that the storage and loss modulus improved with the addition of nano α-Al2O3 loading. TGA and DSC analyses were conducted to recognize the thermal behavior of the composites produced. TGA results illustrated a drastic shift of the weight loss curve towards higher temperature, which led to reduction in the polypropylene heat release rate in both composites. DSC results showed that crystallinity of composites increased with the addition of the Al2O3 nanoparticles. Finally, FTIR study confirmed the existing of Al-O bond at 568 cm-1 resulted from the nano α-Al2O3 particles which were recently created.